Thinking outside the box: CSE in ELT - Gravano, María Paula (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2022)
In recent years, teaching English as a foreign language has presented several challenges for teachers. Not only should students learn the language in a meaningful context, but they should also develop critical thinking skills, creativity, communication and collaboration with a perspective on Comprehensive Sexuality Education. The purpose of the present classroom account is to describe two projects that integrated the use of the English language learned throughout the year with students aged between 11 and 13 while developing awareness towards gender stereotyping and representation. This account shows that if teachers question, complement and deconstruct the materials used for ELT with a more inclusive perspective and design didactic sequences and projects accordingly, Comprehensive Sexuality Education flows naturally in the English classroom.